Cathodic reduction of bisulfite and sulfur dioxide in aqueous solutions on copper electrodes: an electrochemical ESR study. - Streeter, I; Wain, A; Davis, J; Compton, R (2005)
The electrochemical reduction of aqueous solutions of sulfite under acidic conditions on copper electrodes is reported, and a mechanism is proposed. Cyclic voltammetry at a copper disk suggests the operation of two reduction processes, the dominant process depending on solution pH. At very low pH (0-2), sulfur dioxide is reduced in a two-electron, two-proton reaction, but at higher pH (2-5), bisulfite is the electroactive species, being reduced by a single electron to ultimately yield the SO2*- radical anion. Simultaneous electrochemical electron spin resonance (ESR) measurements using a tubular flow cell support this proposal, and suggest that the radical anion is in equilibrium with dithionite, which is found to decay at low pH. Digisim modeling of the system is shown to be consistent with this mechanism over the experimental pH range.